Knowledge acquisition, learning, and the initial pace of internationalization. Issue 1 (February 2015) - Casillas, Jose C.; Barbero, Jose L.; Sapienza, Harry J.
Highlights: We analyze how the pace of internationalization is affected by knowledge and learning activities as firms begin to export. We examine how types of knowledge acquisition and learning interact with one another. We found evidence for significant knowledge-learning interaction effects on the pace of internationalization. Analysis shows that the effects of congenital knowledge are moderated by the age of the firm at initial exporting activity. Results show that the effects of vicarious learning and experiential learning are moderated by firms' strategic intentions. Abstract: We analyze how knowledge, learning, and strategic intent shape export intensity during the period surrounding the initiation of export activities in small, independent firms. Our research is conducted on a sample of small firms started in Andalusia, a region characterized by a lower proportion of exporting firms. By examining the interplay among different forms of knowledge and learning we extend stage and international entrepreneurship models of the internationalization process. We find that in addition to the expected direct effects of learning, different forms of knowledge and learning interact to shape the pace of internationalization. Additionally, we find that pre-existing foreign knowledge influences export intensity in younger firms, but not in older ones; and, that the effects of vicarious learning and experiential learning on export intensity are conditioned by firms' strategic intentions. We discuss the meaning of our results and suggest avenues for future study.